Faceted Classification for Museum Artefacts: A Methodology to Support Web Site Development of Large Cultural Organizations - Ménard, Elaine; Mas, Sabine; Alberts, Inge (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This research project aimed to provide a visual representation of the Artefacts Canada digital collection. The taxonomy creation involved the implementation of an innovative four-step methodology. The resulting user-friendly bilingual taxonomy that will provide worldwide visitors with the mean to better access Canadian virtual museum collections is presented. Ce projet de recherche a pour objectif de représenter visuellement la collection numérique d'Artefacts Canada. La création d'une taxinomie repose sur la mise en œuvre d'une méthodologie novatrice en quatre étapes. Sera présentée la taxinomie bilingue conviviale ainsi créée qui permettra aux visiteurs de partout un meilleur accès aux collections muséales numériques du Canada.